Rehabilitation exercises of different weights and their effect on increasing the range of motion and muscle strength of a joint after suffering a partial tear - Sattar Khalil, Lamyaa Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Sports medicine is the centerand the basic field in monitoring the physical fitness of athletes and preventing them from injuries in addition to treating and rehabilitating, athletes who suffer from previous injuries. The sport medical concept provides suitable methods to estimate the athlete’s health status after injury and the possibility of returning to play again. The importance of physical therapy has increased in the sports field because of its decisive effect in preserving the safety of the player and preventing recurrence of injury. In addition to accelerating the recovery from various injuries, as sports medicine works through therapeutic exercises to increase the player’s functional abilities by using modern sports rehabilitation methods to rehabilitate The player to do the rated muscular effort that facilitates the neuromuscular communication, which leads to raising the efficiency of the nervous system’s control in fine muscular work. Consequently, we find that the use of multiple applications of sports rehabilitation methods to increase the vitality of the affected tissues and urge them to use their potential energy to accelerate recovery from injury. In the research problem,the researcher considers that overload and insufficient warming up in training can be one of the main reasons for increasing the number of injuries in the joints and the orgasm of the athlete’s body. Different types of rupture can act on physiological changes that may affect the work or function of the joint, which leads to the inability of the player to move properly and that, may affect the motor ranges of the joint.As well as,rupture affects muscle strength, and due to the lack of rehabilitation programs and treatment for the treatment of partial rupture of the knee joint, the researcher decided to prepare rehabilitative exercises in order to increase the flexibility and muscle strength of the affected joint.